Leveraging gamification to enhance motivation and engagement among EFL learners - Tsai, Yea-Ru (Universitas Ahmad Dahlan, 2024)
In recent years, gamification has appeared to be an enjoyable and appealing instructional approach in educational settings. This paper reports the implementation and evaluation of gamified instruction to support learners of English as a foreign language in a linguistics course. Several gamification elements, such as experience points, badges, leaderboard and competition, were deployed on a Moodle course management system. A comparison of the results of the survey on learning motivation revealed that the experimental group had greater learning motivation than did the control group after the instruction, particularly in the dimensions of relevance and satisfaction, suggesting that gamification can increase learners’ interest and satisfaction. To illustrate learning engagement, the data of online activities in the course management system were analyzed and compared between groups. The outcomes were encouraging, showing that students in the gamified group were more likely to submit quizzes and posts on discussion forums than were those in the nongamified group. The analysis of the relationships between gamified learning activities and motivation revealed that learning motivation was significantly correlated with discussion forums, WordWall games and badges. The findings indicate that gamification elements can effectively promote students’ motivation and engagement in learning English as a foreign language context.